2019
DOI: 10.30802/aalas-jaalas-18-000057
|View full text |Cite
|
Sign up to set email alerts
|

Welfare and Scientific Considerations of Tattooing and Ear Tagging for Mouse Identification

Abstract: Ear tagging is perceived as less painful or stressful than tattooing and therefore is generally considered less harmful or costly to welfare. However, ear tags are more difficult to read than tattoos and can fall out, and mice usually require restraint for the tag numbers to be read accurately. We assessed the welfare and scientific implications of tattooing by using a commercial device compared with restraint in a device versus ear tagging. Male and female BALB/c mice (n = 32) underwent procedures after 1 wk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…However in the same study, both CD-1 and C3H/He males had greater scores than their female counterparts [ 58 ]. Similarly, male BALB/c mice had higher grimace scores than females [ 69 ]. Alternately, Cho et al [ 65 ] found no sex differences in CD-1 mice, although differences in response to analgesic were noted with females appearing to respond to carprofen with a reduction in grimace score more readily than males [ 65 ].…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
See 2 more Smart Citations
“…However in the same study, both CD-1 and C3H/He males had greater scores than their female counterparts [ 58 ]. Similarly, male BALB/c mice had higher grimace scores than females [ 69 ]. Alternately, Cho et al [ 65 ] found no sex differences in CD-1 mice, although differences in response to analgesic were noted with females appearing to respond to carprofen with a reduction in grimace score more readily than males [ 65 ].…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
“…Cupping or tunnel handling are proposed as alternatives to the traditional method of picking up by the tail [ 78 ]. Perhaps somewhat surprisingly given the reported specificity of the MGS for pain there is some evidence that method of routine handling influences MGS with increased scores in mice handled by the tail compared to those that were tunnel handled [ 69 ]. This contradicts the findings of a previous study where no differences between the two methods were reported [ 67 ].…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
See 1 more Smart Citation
“…This study also provided evidence that tunnel handled mice showed greater exploration in an Open Field Test (OFT) and Elevated Plus Maze (EPM) following a single IP injection in comparison with tail handled mice [11]. In addition, repeated injection [14,16], tattooing or ear-tagging [15], do not negate the beneficial effects of tunnel handling upon voluntary interaction with a handler. A concern identified in the thematic analysis was that respondents believed mice can become more stressed, aggressive or harder to handle after tunnel handling because they have not experienced direct contact with hands.…”
Section: Plos Onementioning
confidence: 80%
“…A single study has shown that handling method can influence glucose metabolism [10], and there are inconsistent results regarding the influence of handling methods upon plasma corticosterone levels from two studies [10,13]. Importantly, single or repeated restraint [7,11,14,15], lifting the tail for abdominal inspection [7] and injection [11,14,16] do not negate the beneficial effects of tunnel handling upon voluntary interaction with a handler. In addition, while most studies have employed daily handling to investigate impacts upon behaviour and physiology, recent studies have shown that weekly or fortnightly handling during cage cleaning is sufficient for mice to show positive responses to tunnel handling [14,16].…”
Section: Introductionmentioning
confidence: 99%